Urban expansion of the municipality of São Miguel do Oeste/SC, in a geomorphological context (Research, Society and Development, 2021)
The municipality of São Miguel do Oeste, West of Santa Catarina state, developed from a hard influence of migratory processes and also through pressure on its natural resources, notably the Araucaria forests. In this sense, the present study aims to analyze the process of urban expansion of São Miguel do Oeste, in a socio-temporal and geomorphological context, in order to contribute to the understanding the man/space/time relationship in the construction of that city. The study of the relief morphology was performed using a Digital Elevation Model (DEM), from which the slope map, the hypsometric map and the topographic profiles were generated. The spatial and temporal analysis was carried out through documents, historical maps and charts filed at the Municipality of São Miguel do Oeste. The beginning of the city's formation was in a flat relief, close to the head of the Guamirim River, and its period of greatest territorial expansion occurred in the 1970s, when the municipality received numerous families who emigrated from Rio Grande do Sul state. the relief in erosive cliffs were the main conditioning factors of the current urban spatial configuration, which boosted the city's vertical growth.